2016
DOI: 10.1007/s00701-015-2686-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of medium and large petroclival meningiomas: benchmark and limits

Abstract: Da Li and co-workers present a detailed sub-analysis of their series of petroclival meningiomas, which is the largest monocentric series published to date [5,6]. In the current work, they restrict the analysis to medium and large tumours of more than 2 cm in diameter-the tumours that really cause difficulties for microsurgery as well as stereotactic radiosurgery. Gross total resection was achieved in 56 % of patients; dysfunctions of the cranial nerves were the most common complication and occurred in two-thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…In terms of the surgical approaches, the subtemporal transtentorial approach (STA) and the Kawase approach (KA) have the characteristics of short operative distance, convenient tumor base resection and less intraoperative bleeding but with the limitation for large posterior petrosal PCMS; the retrosigmoid approach (RSA) has the feature of fewer approach-related complications while the restriction to the petroclival region; the anterior sigmoid approach (ASA), also named the posterior petrosal approach (PPA), can facilitate the exposure of tumors, reduce the traction of the brainstem but perplexes the neurosurgeons for harder maneuver. Although there are many surgical approaches for PCMs and the relevant studies have repeatedly reported, the optimal choice for the operation is of extreme difficulty (2)(3)(4)(5) and no uniform standard establishing the superiority of one approach over another is acknowledged currently (6,7), due to the anatomical complexity, the multiformity of tumor invasion and the intricacy of a balance between neurofunctional preservation and tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the surgical approaches, the subtemporal transtentorial approach (STA) and the Kawase approach (KA) have the characteristics of short operative distance, convenient tumor base resection and less intraoperative bleeding but with the limitation for large posterior petrosal PCMS; the retrosigmoid approach (RSA) has the feature of fewer approach-related complications while the restriction to the petroclival region; the anterior sigmoid approach (ASA), also named the posterior petrosal approach (PPA), can facilitate the exposure of tumors, reduce the traction of the brainstem but perplexes the neurosurgeons for harder maneuver. Although there are many surgical approaches for PCMs and the relevant studies have repeatedly reported, the optimal choice for the operation is of extreme difficulty (2)(3)(4)(5) and no uniform standard establishing the superiority of one approach over another is acknowledged currently (6,7), due to the anatomical complexity, the multiformity of tumor invasion and the intricacy of a balance between neurofunctional preservation and tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%